AMPLIFIKASI FRAGMEN 0,4 KB DAERAH D-LOOP DNA MITOKONDRIA LIMA INDIVIDU SUKU BALI TANPA HUBUNGAN KEKERABATAN DENGAN METODE POLYMERASE CHAIN REACTION (PCR) - K. Ratnayani; Sagun Chandra Yowani; Liangky Syane S (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
The human mitochondrial DNA (mtDNA) has higher polimorfism level than nucleous genom, and it ismaternally transmitted. D-Loop is a non-sense region in human mtDNA that has the highest polimorfism. Generally,the aim of this research is to find out the variation in D-Loop region of mtDNA in some Balinese without familycorrelation. For that reason, this research was brought out to determine the sequences of nucleotide of D-Loop regionin five normal Balinese from different families without correlation. The specific aim of this research is to amplify the0,4 kb fragment of mtDNA D-Loop region in five Balinese above, using the PCR methode. In conducting the PCR,the temperature of annealing of primer and the weight of template of mtDNA were optimized. Several phases thathave been conducted : 1). Lisis of the cavum oris epithelium; 2). Quantation of DNA; 3). Reaction PCR; 4). Result ofPCR detection with agarosa gel electroforesisThe result of this research is the amplification of 0,4 kb fragment of D-Loop region in mtDNA by PCR.This research also found the optimum temperature annealing, which was 55 0C, and the optimum weight of templateof DNA which was ± 0,688 ?g.